DENETİM GÖREVLİLERİNİN UYMASI GEREKEN ETİK İLKELER - (:unkn) unknown (My University, 2014)
Kamu görevlilerinin görevlerini yerine getirirken uymaları gereken temel kurallar hukuk kurallarıdır. Kamu yönetiminde değişen anlayış dolayısıyla uyulması gereken kurallar arasında etik kurallar da etkili olmaya başlamıştır. Bu etik kurallar hukuk kuralı haline de getirilmiştir. Özellikle denetim görevi yürütenler bakımından söz konusu hukuk kuralları ayrıca etik ilkeler olarak belirlenmiştir.

The basic rules which must be abided by public officers are rules of law. Due to changing understanding of public administration, rules of ethics had started to be effective in the rules which must be abided. These rules of ethics were transferred to rules of law too. Especially these rules of laws have designated as ethical principles for public officers who work at task of inspection.
THE ETHICAL PRINCIPLES WHICH MUST BE ABIDED BY PUBLIC AUDITORS
Keywords: Etik; Hukuk; Kamu Yönetimi